Potentials of Alginates as Capping Agent for Oral Colon Delivery of Radiosynthesized Silver Nanoparticles: A Review - D. P. Perkasa; W. Arozal; M. Suhaeri (PPIKSN-BATAN, 2022)
Radiosynthesized silver nanoparticles (AgNPs) offer benefits for treatment of chronic colon inflammation due to their anti-inflammatory activity. Targeted delivery of AgNPs to the colon allows topical treatment at high concentration but at reduced systemic side effects. Meanwhile, related to drug administration, oral route is a common method. However, the physiology of the gastrointestinal (GI) tract limits the AgNPs ability to achieve their therapeutic level. This is specifically related to the acidic environment of the stomach and mucus layer of the GI tract. Concurently, alginates are one of the most extensively explored biomaterial classes for drug delivery system due to its biocompatibility, gel-forming ability at mild condition, anionic nature, sensitivity, and mucoadhesiveness. In this review we provide an overview of appropriate features of alginates as capping agent for oral delivery of radiosynthesized AgNPs to the colon. As capping agents, alginates play multiple roles specific to its processing stages, i.e., radiosynthesis, stabilization of nanoparticle system, and oral colon delivery devices of AgNPs. Additionally, we describe outstanding features of alginates as capping agents for drug delivery device as well as the positive contributions of radiation processing on improving the functional effects of alginate.